Pengembangan Perangkat Pembelajaran Keanekaragaman Hayati Berbasis Web Di SMAN 6 Makassar dan SMAN 2 Maros - Makmun, Nurlindah; Ismail, Ismail; Adnan, Adnan (Universitas Negeri Makassar, 2018)
Abstract.Â Development of Web-Based Biodiversity Learning Tool Class of SMA X. This research is a type of research using research and development (R & D) research using ADDIE model consisting of analysis, design, development, implementation, and evaluation. The subjects of the study were validator, students of SMAN 6 Makassar and SMAN 2 Maros each - 2 classes namely Class X MIA 1 and Class X IPS 2 with teacher Biology in SMA each data analysis technique that is statistical analysis. The developed product is motivated by curriculum and development of information and communication technology (ICT). This product will further emphasize the students to be independent in learning because of the activities and learning provided. This development aims to produce learning tools, training activities, create tasks, create materials, Web media e-learning using a Moodle system (classbiology.com) that is valid and practical. learning tools that generate high validation of the field with the validity of the validity of the value of syllabus 4.18, Learning Implementation Plan (RPP) obtained validity value 4.37, Worksheet (LKPD) obtained validity value 4.1, materials or teaching materials obtained the value of validity 4,01 and web-based Moodle obtained validity value 4.23. Keywords: web, learning device, Moodle, ADDIE